Multilevel diversity coding with distortion - Yeung, R.W. (IEEE transactions on information theory, 1995)
In a Diversity Coding System, an information source is encoded by a number of encoders. There are a number of decoders, each of which can access a certain subset of the encoders. We study a diversity coding problem in which there are two levels of decoders. The reconstructions of the source by decoders within the same level are identical, and are subject to the same distortion criterion. Our results imply a principle of superposition when the source consists of two independent data streams. Practical codes achieving zero error can easily be constructed for this special case. A class of open problems on this topic is also suggested.< >